Mutations in chaperonin-like BBS genes are a major contributor to disease development in a multiethnic Bardet-Biedl syndrome patient population - Billingsley, Gail; Bin, Jenea; Fieggen, Karen J.; Duncan, Jacque L.; Gerth, Christina; Ogata, Koji; Wodak, Shoshana S.; Traboulsi, Elias I.; Fishman, Gerald A.; Paterson, Andrew; Chitayat, David; Knüppel, Tanja; et al. (Journal of medical genetics, 2010)
Background Bardet-Biedl syndrome is a pleiotropic disorder with 14 BBS genes identified. BBS1, BBS2, BBS4, BBS5, BBS7, BBS8, and BBS9 form a complex called the BBSome, which is believed to recruit Rab8GTP to the primary cilium and promote ciliogenesis. The second group, the chaperonin-like proteins BBS6, BBS10, and BBS12, have been defined as a vertebrate-specific branch of the type II chaperonin superfamily. These may play a role in the regulation of BBSome assembly. - Methods and results Using sequence analysis, the role of BBS6, 10 and 12 was assessed in the patient population comprising 93 cases from 74 families. Systemic and ocular phenotypes were defined. In the study, chaperonin-like BBS gene mutations accounted for the disease in approximately 36.5% of BBS families. A total of 38 different non-polymorphic exonic sequence variants were identified in 40.5% of BBS families (41.9% cases), of which 26 were novel (68%). Six cases had mutations present in more than one chaperonin-like BBS gene. One case with four mutations in BBS10 had a phenotype of overall greater severity. The phenotypes observed were beyond the classic BBS phenotype as they overlapped with characteristics of MKKS (congenital heart defect, vaginal atresia, hydrometrocolpos, cryptorchidism), as well as Alström syndrome (diabetes, hearing loss, liver abnormalities, endocrine anomalies, cardiomyopathy). - Conclusions While overlap between the MKKS and BBS phenotypes has previously been reported for cases with BBS6 mutations, we also observed MKKS phenotypes involving BBS10 and BBS12 and Alström-like phenotypes associated with mutations in BBS1, BBS2, BBS6, BBS7, BBS9, BBS10 and BBS12 for the first time.
Gesehen am 02.02.2023